Implementation of entrepreneurship education in Madrasah Aliyah Negeri 2 in Bandar Lampung - Rosa, Kemala Sandi; Pahrudin, Agus; Koderi, Koderi (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This research explores in detail each of the PDCA stages with reference to the concept of entrepreneurship and how it is implemented at MAN 2 Bandar Lampung. Research methodology: This research uses a qualitative approach, this type of research is a case study. Data sources consist of primary and secondary data. Data collection procedures through observation, interviews and documentation. Data analysis uses data reduction (Data Reduction), data presentation (Data Display), Conclusions: Drawing / Verifying. Results: The results showed that the implementation of entrepreneurship education in Madrasah Aliyah Negeri 2 in Bandar Lampung provides many benefits, but cannot be separated from several obstacles that need to be overcome. The lack of adequate infrastructure and facilities is one of the main obstacles, limiting the school's ability to organize optimal entrepreneurship activities. Teacher support and understanding are also key factors, as a lack of commitment or understanding can hinder program implementation. Students' limited knowledge and skills, especially related to entrepreneurship, are also barriers that need to be addressed. Additional efforts may be needed to improve students' understanding of business concepts and the practical skills required. Challenges in integrating the curriculum, limited financial resources, and the unsustainability of local industry involvement are also barriers that require special attention.